Mitigating the Impact on Users’ Privacy Caused by over Specifications in the Design of IoT Applications - Alfredo Pérez Fernández; Guttorm Sindre (Sensors, 2019)
Privacy has long been an important issue for IT systems that handle personal information, and is further aggravated as technology for collecting and analyzing massive amounts of data is becoming increasingly effective. There are methods to help practitioners analyze the privacy implications of a system during the design time. However, this is still a difficult task, especially when dealing with Internet of Things scenarios. The problem of privacy can become even more unmanageable with the introduction of overspecifications during the system development life cycle. In this paper, we carried out a controlled experiment with students performing an analysis of privacy implications using two different methods. One method aims at reducing the impact of overspecifications through the application of a goal-oriented analysis. The other method does not involve a goal-oriented analysis and is used as a control. Our initial findings show that conducting a goal-oriented analysis early during design time can have a positive impact over the privacy friendliness of the resulting system.